Zapleti z gravitacijsko konstanto - Strnad, Janez (Obzornik za matematiko in fiziko, 2014)
Recently in the CODATA list of fundamental constants the relative uncertainty of the gravitational constant ?$\mathcal{G}$? has been increased twice. The differences between measured values are greater then the quoted uncertainties. ?$\mathcal{G}$? is the most uncertain of all fundamental constants. The constant has been measured also at the International Bureau of Weights and Measures. Very precise measurements are interesting also from the viewpoint of physics.
Keywords: fizika; physics; osnovne konstante; gravitacijska konstanta; relativna negotovost